2003
DOI: 10.1182/blood-2002-09-2790
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of cytogenetic clonal evolution in patients with chronic myelogenous leukemia on imatinib mesylate therapy

Abstract: Cytogenetic clonal evolution (CE) is a known poor prognostic factor in Philadelphia chromosome-positive chronic myelogenous leukemia (Ph-positive CML). However, its prognostic relevance in the era of imatinib therapy is unknown. We investigated the independent prognostic relevance of CE in 498 patients with Phpositive CML treated with imatinib for chronic or accelerated phases. One hundred twenty-one patients had CE alone (n ‫؍‬ 70) or with other accelerated phase criteria (n ‫؍‬ 51). Patients were compared in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
129
3
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(148 citation statements)
references
References 35 publications
8
129
3
8
Order By: Relevance
“…A failure to achieve MCR is associated with an increased risk of disease progression on imatinib. 32,33 Although the deletion status of the cohorts in which this progression is described is not known, the data are compatible with the reduced rate of MCR and increased risk of disease progression that we observed in our patients, both in CP and advanced phase CML.…”
Section: Discussionsupporting
confidence: 73%
“…A failure to achieve MCR is associated with an increased risk of disease progression on imatinib. 32,33 Although the deletion status of the cohorts in which this progression is described is not known, the data are compatible with the reduced rate of MCR and increased risk of disease progression that we observed in our patients, both in CP and advanced phase CML.…”
Section: Discussionsupporting
confidence: 73%
“…31,33,39,40 Apart from a few patients with complex karyotype abnormal- Figure 2 Relevance of FFI and full-blown MF to the probability of a cytogenetic or molecular response and the risk of acceleration or death of patients. Among the patients with FFI or MF before or within the first 3 months after the start of imatinib treatment, the probability of achieving a complete cytogenetic or major molecular response was markedly reduced compared to the patients with an initial normal fiber content ((a) complete cytogenetics of major molecular response after detection of FFI or MF before the start of imatinib treatment).…”
Section: Discussionmentioning
confidence: 99%
“…Additional chromosome aberrations besides t(9;22)(q34;q11) indicate clonal evolution of disease [39][40][41] and are usually regarded as an indicator of loss of efficacy of treatment. 31,33,39,40 Apart from a few patients with complex karyotype abnormal- Figure 2 Relevance of FFI and full-blown MF to the probability of a cytogenetic or molecular response and the risk of acceleration or death of patients.…”
Section: Discussionmentioning
confidence: 99%
“…126 Early kinetics of the BCR-ABL fusion allow prognostic predictions after SCT: a slow reduction of the BCR-ABL transcripts on days þ 28 and þ 56 showed a significant correlation with higher relapse rates, whereas the achievement of PCR negativity after SCT was associated with stable long-term remissions in a study of Lange et al 129 Asnafi et al 130 determined a threshold of 10 À4 of BCR-ABL/ABL on day þ 100 after SCT to predict the probability of relapse, and another study showed higher relapse rates when BCR-ABL fusion transcripts were detected within the first 3-5 months after SCT. 131 Resistance to TKI can be mediated by different mechanisms, for example, point mutations in the ABL gene, [132][133][134] which can be revealed by sequencing after screening by high performance liquid chromatography. The ELN formulated clear indications: screening is indicated in cases where patients fail to achieve major cytogenetic response (reduction of Ph-positive metaphases o35%) at 12 months or show loss of molecular response as defined by an increase in the BCR-ABL/ABL ratio of X1 on a logarithmic scale.…”
Section: CMLmentioning
confidence: 99%